Sportwissenschaft - Cassel M; Brecht P; Günther K-P; Mayer F (Deutsche Zeitschrift für Sportmedizin)
Joint replacement surgery has showna tremendous increase within the last decades. Advanced operation techniques and modern implants support operative treatment of younger patients with increased demands during daily-living, leisure time as well as sports activity. Physical activity after total joint replacement is generally recommended. This leads to improved osteointegration of the prosthesis, decreased loosening rates, enhanced muscular performance and a reduced cardiovascular risk. Potential recommendations regarding suitable activitiesand intensities depend on the affected joints, surgical techniques, implantsusedas well as accompanying pathologies. While low-impact-sport with mainly cyclic endurance activity is generally recommended, high-impact-sport can only be permitted with previous experience and atcertain arthroplasty sites. Due to high risk of injuries participation in contact and game sports should generally be avoided.KEY WORDS: Sport Recommendation, Physical Activity, Joint Replacement, Prosthesis, Patients